Livestock Mobility Through Integrated Beef Production-Scapes Supports Rangeland Livestock Production and Conservation - Barry, Sheila (Frontiers in Sustainable Food Systems, 2021)
Much of the world's rangelands contribute to food production through extensive grazing systems. In these systems, livestock producers, pastoralists and ranchers move grazing animals to access variable feed and water resources to create value while supporting numerous other ecosystem services. Loss of mobility due to political, social, ecological, and economic factors is documented throughout the world and poses a substantial risk to rangeland livestock production and conservation of rangeland resources. The integration of production-scapes can facilitate livestock mobility through transportation and trade. This paper describes the beef cattle production system in California, where transporting and marketing animals integrate an extensive grazing system with intensive production systems, including feeding operations. Analysis of livestock inspection data quantifies the magnitude of livestock movements in the state and the scope of production-system integration. Over 500,000 head – 47 percent of the state's calf crop – leave California rangelands and are moved to new pastures or feedyards seasonally over a 12-week period each year. Most ranchers in California, from small-scale producers (1 to 50 head) to larger producers (more than 5000), participate in the integrated beef production system. Less than 1% of steers and heifers go from rangeland to meat processing. Like pastoralists, ranchers strategically move cattle around (and off) rangeland to optimize production within a variable climate. Ranchers indicate that their movements result from changes in forage quality and quantity and support their desire to manage for conservation objectives, including reducing fire fuels, controlling weeds, and managing for wildlife habitat. Inspection data, as well as direct observation, interviews, and surveys within the San Francisco Bay area, reveal the extent to which the region's ranchers rely on saleyards to facilitate the movement of cattle and integration of production systems. Saleyards and cattle buyers drive beef production efficiency by sorting, pricing, and moving cattle and matching them to feed resources in more intensive production systems. However, transactions lack traceability to inform policy and consumer choice. New data technologies like blockchain can provide traceability through integrated production-scapes and facilitate market development to support grazing landscapes and consumer choice.